Application of fractional algorithms in control of a quad rotor flight - Coelho, J. (2019)
This paper studies the application of fractional algorithms in the control of a quad-rotor rotorcraft machine. The main contribution of this paper focuses in the development a flight simulator to provide the evaluation model of the quad-rotor. Several basic maneuvers are investigated, namely the elevation and the position control.